2008
DOI: 10.1590/s1676-26492008000600002
|View full text |Cite
|
Sign up to set email alerts
|

Estado de mal epiléptico

Abstract: INTRODUÇÃO: O estado de mal epiléptico (EME) é subdiagnosticado, especialmente as formas clínicas com sinais motores sutis ou apenas com alteração da consciência. É uma emergência neurológica que necessita diagnóstico imediato e a tratamento agressivo e para prevenir lesão neuronal. OBJETIVOS: Revisar, discutir e propor protocolo para o tratamento desta condição. METODOLOGIA: A literatura foi selecionada a partir de pesquisa nas bases de dados MEDLINE e PUBMED. RESULTADOS: Propomos um protocolo utilizando diaz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 18 publications
(16 reference statements)
0
14
0
4
Order By: Relevance
“…It is usually recommended that a longer acting non-lipophilic drug that does not promote accumulation after repeated use, such as phenytoin or fosphenytoin, be administered immediately after diazepam when seizures persist or even when they have been aborted. 9,46 …”
Section: Initial Treatment (First-line)mentioning
confidence: 99%
See 1 more Smart Citation
“…It is usually recommended that a longer acting non-lipophilic drug that does not promote accumulation after repeated use, such as phenytoin or fosphenytoin, be administered immediately after diazepam when seizures persist or even when they have been aborted. 9,46 …”
Section: Initial Treatment (First-line)mentioning
confidence: 99%
“…in bolus in adults, and 15 mg/kg in the elderly, 3 preferably without dilution, with a maximal rate of administration of 50 mg/min in adults and 20 mg/min in the elderly due to the possibility of occurrence of significant hypotension and arrhythmias. 5,46 Fosphenytoin, the phosphate ester of phenytoin, unlike phenytoin, is a highly water-soluble prodrug, with a near physiological pH. After i.v.…”
Section: Initial Treatment (First-line)mentioning
confidence: 99%
“…In Brazil, the annual occurrence of SE is about 90 000 cases 101. Thus, increased awareness of presentation, etiologies and treatment of SE is essential in the practice of critical care medicine.…”
Section: Brain Lesions At Early Developmentmentioning
confidence: 99%
“…[5] Garzon conceptualized the status epilepticus as a seizure lasting more than or equal to 30 minutes or repeated shorter duration of crises but without regaining consciousness. [6] The neurological monitoring of patients with SAH initiated a new strategy for the early detection of cerebral vasospasm, more feared and disabling complication of this disease. Vespa et al (2005) conducted a study in 32 patients with SAH, which found a decrease in quantitative variability relative of alpha waves (AR) in 100% of patients with vasospasm, angiographically confirmed in 10 of 19 patients, a decrease of AR preceded the clinical diagnosis of vasospasm in 2.9 days.…”
Section: Introductionmentioning
confidence: 99%